Ladybird Histories :Ancient Egyptians - Adams, Simon
This Ladybird Histories book all about Ancient Egypt is perfect for children learning about Ancient Egypt and the Egyptians at school. It includes Ancient Egypt's kings and queens, how ancient Egyptians lived, and why they believed in mummification and different Egyptian gods. It's packed full of interesting and entertaining details that will delight all readers—from lifestyles, battles, and important characters to the influence the past has played on the world around us today— and has everything you need to know about Ancient Egypt for school homework!.